1990
DOI: 10.1002/ardp.19903230303
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Inhibiting [1,2‐Bis(fluorophenyl)ethylenediamine]platinum(II) Complexes Part II: Biological Evaluation ‐in vitro Studies on the P 388 D1 Leukemia Cell Line

Abstract: Experiments on the P 388 D1 cell line (48 h exposure) demonstrate that [1,2-bis-(fluorophenyl)ethylenediamine]platinum(II) complexes are comparably active on the cell number and 3H-thymidine incorporation, irrespective of the position of the fluorine atom (ortho, meta, or para) and the nature of the "leaving group" (Cl- or H2O). However, the compounds of the R,R/S,S series are more active than those of the R,S series and comparable to cisplatin. In the "tumor colony forming assay" the R,R/S,S configurated comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…25,26 Particularly, it has been reported that optically pure (1,2-diarylethane-1,2-diamine)dichloroplatinum(II) complexes induce significant inhibitory effects on the growth of leukemic and tumor cells, and a distinctly better effect was generally observed with the R,R/S,S configurations compared with the R,S counterparts. [27][28][29][30] These results motivated us to apply the findings from platinum(II) complexes to iridium(III) complexes. In this manuscript, we report the synthesis of novel dichlorobis[enantiopure 1,2-diarylethane-1,2-diamine]iridium(III) chlorides (general formula see Graphic Abstract) and their antiproliferative effects on a panel of representative human solid tumor cell lines.…”
Section: Introductionmentioning
confidence: 90%
“…25,26 Particularly, it has been reported that optically pure (1,2-diarylethane-1,2-diamine)dichloroplatinum(II) complexes induce significant inhibitory effects on the growth of leukemic and tumor cells, and a distinctly better effect was generally observed with the R,R/S,S configurations compared with the R,S counterparts. [27][28][29][30] These results motivated us to apply the findings from platinum(II) complexes to iridium(III) complexes. In this manuscript, we report the synthesis of novel dichlorobis[enantiopure 1,2-diarylethane-1,2-diamine]iridium(III) chlorides (general formula see Graphic Abstract) and their antiproliferative effects on a panel of representative human solid tumor cell lines.…”
Section: Introductionmentioning
confidence: 90%
“…Protection against nucleophilic attack can be achieved by using molecular modelling techniques to generate a shield effect around the platinum atom. This protection due to the steric hindrance of the ligand has been put forward to explain the lower reactivity of compound (19a) towards reactive biological compounds [113]. However, it has to be kept in mind that avoiding these undesirable reactions could also result in a negative effect on binding to DNA, leading to less active complexes.…”
Section: Analytical Techniques As Basis For the Drug Development Processmentioning
confidence: 99%
“…1. [14,18,24,25]. Despite the ionic nature of the diaqua(1,2-diphenylethylenediamine)platinum(II) sulfates, their water solubility is quite low because of the contribution of the large, hydrophobic neutral ligand.…”
Section: Drugsmentioning
confidence: 99%